From Small Change To A Blessing: A Study Of Infaq And Shodaqoh By Lazisnu In The Village Of Telogorejo, East Lampung - Wulandari Putri, Nurul; Shalma Zahira, Inggis (Nuban Jagadhita Centre, 2025)
Purpose: This study analyzes the role of the Nahdlatul Ulama Zakat, Infaq, and Shodaqoh Institution in managing infaq and shodaqoh to improve the welfare of the community in Telogorejo Village, East Lampung. Infaq is defined as the giving of wealth for Islamic social activities, while shodaqoh is voluntary giving without expectation of reward. LazisNU, as a NU philanthropic institution, focuses on collecting and distributing funds to alleviate poverty and support social justice. The purpose of this study is to understand the strategies for managing infaq and shodaqoh funds and their impact on rural communities. Methodology: The method used is a descriptive qualitative approach, with data collection through interviews, observation, and documentation studies. Findings: The results show that LazisNU Telogorejo Village, which was founded in 2022, has successfully collected funds through the coin NU program, which is a simple infaq box distributed to residents' homes and collected monthly. These funds were distributed for consumptive assistance, such as death benefits, health assistance, and support for the elderly, although productive distribution has not yet been achieved due to limited funds. Supervision and reporting were carried out transparently to maintain accountability.